Immunomodulatory activities of Clausena excavata Burm. f. wood extracts - Manosroi A. (2014)
In vitro immunomodulatory activities of aqueous extract, acetone extract and the Thai folklore extract of Clausena excavata Burm. f. on mouse immune system were investigated. The phagocytic activity of macrophages and splenocyte proliferation in the absence and presence of mitogens (lipopolysaccharide, LPS) or pokeweed mitogen, PWM) were assayed. The aqueous extract exhibited the maximum effect on both respiratory burst response and lysosomal enzyme activity more than the acetone extract and the Thai folklore extract indicating effective phagocytic activation. For splenocyte proliferation assay, the Thai folklore extract with LPS gave the maximum activity higher than that with PWM, suggesting specificity towards B cell proliferation through T cell independent pathway the same as LPS. The present study revealed the immumunomodulating activity, which could be explained the traditional use of this plant in Thailand. © 2003 Elsevier Ireland Ltd. All rights reserved.